Cobalt(II), copper(II), nickel(II) and zinc(II) complexes of two novel Schiff base ligands and their antimicrobial activity - Çukurovali, A; Yilmaz, I; Özmen, H; Ahmedzade, M (Kluwer Academic Publ, 2002)
Two new, Schiff base ligands containing cyclobutane and thiazole rings, 4-(1-methyl-1-mesitylcyclobutane-3-yl)-2-(2,4-dihydroxybenzylidenehydrazino)thiazole ((LH)-H-1) and 4-(1-methyl-1-mesitycyclobutane-3-yl)-2-(2-hydroxy-3-methoxybenzylidenehydrazino)thiazole ((LH)-H-2) and their mononuclear complexes with a 1:2 metal-ligand ratio have been prepared with acetate salts of Co-II, Cu-II, Ni-II and Zn-II in EtOH. The structures of the ligands and their complexes have been established by microanalyses, i.r., u.v.-vis., C-13- and H-1-n.m.r. spectra, and by magnetic susceptibility measurements. The complexes are mononuclear. Thermal properties of the ligands and complexes have been studied by t.g.a. and d.s.c. techniques. Antimicrobial activities of the ligands and their complexes have been tested against eight different microorganisms. Some of the complexes and (LH)-H-1 were found to be active against some of the microorganisms studied.
Keywords: Metal-Complexes; Derivatives